Legal Protection for Citizens Affected by The Termination of Access Policy of Unregistered Private Scope Electronic System Operators - Wiryawan, Rinalvin Achmad; Istislam, Istislam; Uyun, Dhia Al (IJBLE Scientific Publications Community Inc., 2024)
On July 30, 2022, the government's policy in terminating access to unregistered private scope electronic system operators to several internet platforms including: Paypal, Yahoo, Epic Games, Steam, Dota, Counter Strike, Xandr.com, and Origin, has resulted in material and immaterial losses to citizens who use the platform of unregistered private scope electronic system operators. The government's policy in terminating access or blocking access to PSE LP, harms the digital rights of citizens. Blocking has an impact on the inaccessibility of services and loss of revenue due to termination of PSE LP access. Citizens are eligible for legal protection, which includes preventive and repressive legal protection. Preventive protection includes the right to communicate and access information guaranteed in human rights provisions. Repressive protection includes the right to legal guarantees for legal remedies in filing state administrative court lawsuits.